Parenting and emotional well-being of adoptive school-aged children: The mediating role of attachment - Santos-Nunes, Marta (2017)
This study focuses on the processes of adoptive parenting that affect children's emotional well-being. It aims to analyze the role of children's attachment as a mediator of the relationship between both parenting styles and parenting stress and children's positive and negative affect in adoptive families of school-aged children. The study included 322 Portuguese participants, divided into one group of adoptive parents (n = 135) and one comparison group of non-adoptive parents (n = 187); target-children were aged between 6 and 12 years. Self-report questionnaires were used to analyze the dimensions under study (parenting styles, parenting stress, children's attachment and children's emotional well-being). After conducting a preliminary analysis to identify potential differences between the adoptive and the non-adoptive parents, a mediation model was tested using the path analysis procedure. A baseline model was established, followed by a multi-group analysis in order to explore the model's invariance across the groups. Children's attachment mediated the relationship between parenting (styles and stress) and children's positive and negative affect. The multi-group analysis revealed that, for the adoptive group, both secure and anxious/ambivalent attachment mediated the association between parenting stress and negative affect; for the non-adoptive group, secure attachment was found to mediate the link between emotional warmth and positive affect. For both groups, the relationship between parenting stress and positive affect was mediated by secure attachment. Results pointed to the relevance of children's attachment in the association of parenting styles and parenting stress with children's emotional well-being. Moreover, differences concerning the mediation model emerged across the two groups, revealing that children's negative outcomes were better explained in the adoptive group. The results reinforce the importance of supporting adoptive parents after the adoption process.